The Impact of Islamic Ideology in the Society Based on Pottery Designs of Islamic Middle Ages - Babak Behshid; Reza Rezalou; Karim Hajizadeh; Behrouz Afkhami (Anastasis: Research in Medieval Culture and Art, 2022)
The art of pottery in the Islamic Middle Ages along with other arts is one of the most beautiful and important manifestations of Islamic teachings that has affected all aspects of human life; theology, attention to the universe, goodness and humanity are constantly commanded. In this research, an attempt is made to determine the extent of the effect and type of those teachings by studying and classifying the motifs and decorations of pottery of the Islamic era based on the concepts of Quranic verses. The type of analytical-descriptive research and the method are field work and library research. After classifying the verses of the Islam, the designs and decorations of the art of the Islamic period and matching them with each other, a logical analysis of the findings is conducted. The aims of the research include: separating the types of motifs and decorations of works of art related to the Islamic period influenced by the themes of Islamic ideology and finding the extent of these effects. Questions such as the effect of the Islamic ideology on the pottery decorations of the Islamic era and their types will be addressed. The purpose of addressing the Islamic teachings on pottery was answered assuming religious beliefs, philanthropy and the taste of pottery artists.